Tren Berjilbab Kalangan Muda Muslimah Urban di Yogyakarta: Tinjauan Antropologi Islam Talal Asad - Muhammad Arman Al Jufri (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
This article examines the hijab trend among young urban Muslim women in Yogyakarta. This trend in practice is not only related to religious practice. This trend is also related to the existentialist aspect, namely identity as a true Muslim woman. The choice of urban Muslim women's hijab, both size, and model, is an indicator of the relationship of existentialist aspects to this trend. This research uses qualitative methods with this type of field study. To see it, the author uses the Islamic anthropology Talal Asad. Two points are outlined; first, what and how is the basis of Islamic reason (Qur'an and Hadith) when talking about hijab; second, how and to what extent discourse and social relations affect the meaning of the veiled trend. As a result, Q. 24:31 and Q. 33:59 are two verses of the Qur'an that specifically speak of this term. Both are used in legitimizing the legal status of the hijab (closing the aurat). Understanding the two verses has two tendencies, some interpret the verse in a strict sense; textual, others tend to be more adjective; non-textual. The trend of hijab among young urban Muslim women in Yogyakarta has a meaning not only limited to the problem of carrying out religious orders as stated in the Qur'an, but also related to identity status, the ideology that accompanies it, and the process of commodification.